Can industrial policy work under neopatrimonial rule? - Tilman Altenburg (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Technological latecomer countries face a dilemma,they need to pursue pro-active industrial policies to compensate for manifold disadvantages vis-à-vis established competitors, but at the same time, due to neopatrimonial politics and capacity constraints, their institutions are rarely in a position to correct market failure effectively. Do the risks of misallocation outweigh the benefits and should these countries abstain from industrial policies? Country studies show that selective industry support is indeed frequently used as a source of patronage and clientelism, and implementation is often ineffective. Two of the surveyed countries - Tunisia and Ethiopia - with neopatrimonial traits nevertheless pursue ambitious agendas of industrial modernization and implement them fairly effectively. Scarcity of fossil energy and mineral resources, the need to build legitimacy on increasing social welfare, and committed leadership distinguish them from worse performers.
Keywords: L52; O14; 330; industrial policy; political economy; neopatrimonialism; developing country; Tunisia; Ethiopia